Estimation of the construction period of the buildings (construction period) in the canton of San José by analysis of aerial photographs - Blanco Saenz, Silvia Patricia (2021)
The city of San José in 2017 contained a number of 84,004 buildings, of which their construction period is unknown, the objective of the investigation was the temporary dating of each structure, in order to obtain results that show the distribution links, corresponding to the publication of the Seismic Codes of Costa Rica. Part of the obtained results contains very high numbers of buildings that do not use any of the codes and then, much of the urban expansion made use of the 1974 and 1986 codes, contrary to the number of buildings that followed the rules of the latest updates. Taking into account the foregoing, it is essential for the future that not only the Public Administration consider the evaluation of the infrastructure of its institutions, but also the private and civil sectors to be heading down in the same direction.